2018
DOI: 10.29244/jitkt.v9i2.19295
|View full text |Cite
|
Sign up to set email alerts
|

AMINO ACID PROFILE AND BIOACTIVE COMPOUNDS OF SEAHORSE Hippocampus comes

Abstract: Keywords: H. comes, proximate analysis, amino acid, and bioactive compounds ABSTRAKKuda laut merupakan salah satu sumberdaya hayati laut yang banyak dimanfaatkan sebagai ikan hias, bahan obat tradisional, dan cindera mata. Tujuan penelitian adalah untuk menentukan kandungan proksimat kuda laut segar dan kering, menentukan profil asam amino hidrolisat dan tepung kuda laut, dan menentukan kandungan senyawa bioaktif dari ekstrak etanol kuda laut secara kualitatif. Sampel penelitian ini adalah kuda laut yang didap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
(9 reference statements)
3
11
0
Order By: Relevance
“…The study also reported that seahorses are the highest-mentioned marine resources used to cure illnesses such as asthma, heart-related diseases, dysfunction, wounded in body, reduces body temperature, detox, and skin disease problems. Supported by past research, which demonstrated that seahorses have numerous nutrients for human health with bioactive content that can function as anti-cancer agents, anti-fatigue, anti-aging (Sari et al, 2018) asthma, heart, thyroid, and skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that seahorses are the highest-mentioned marine resources used to cure illnesses such as asthma, heart-related diseases, dysfunction, wounded in body, reduces body temperature, detox, and skin disease problems. Supported by past research, which demonstrated that seahorses have numerous nutrients for human health with bioactive content that can function as anti-cancer agents, anti-fatigue, anti-aging (Sari et al, 2018) asthma, heart, thyroid, and skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The steroid and triterpenoid were analyzed using the Liebermann–Buchard method. Saponin and tannin contents were analyzed using magnesium (Mg) and flavonoids were analyzed using chloride acid (HCl) and amyl alcohol [ 5 ]. Detection and quantification of amino acids were conducted using the HPLC detector fluorescence and HPLC PDA.…”
Section: Methodsmentioning
confidence: 99%
“…There are more than 50 species of seahorses worldwide [ 3 ], and 33 species are found in Indonesia [ 4 ]. One of the seahorse species in Indonesia is the Hippocampus comes L. (HCL), which is the most used in traditional medicine because of its medicinal value [ 5 7 ]. In Indonesia, HCL is used in traditional medicine as a “Jamu” [ 4 ] because it has biocompounds including the aphrodisiac effect, respiratory system, immune system, and antioxidant, antifatigue, and anti-inflammatory properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations